Identifying Dementia research priority for Qatar national dementia research plan: A Cross-sectional Survey - Al Hamad, Hanadi; Sathian, Brijesh (Nepal Journal of Epidemiology, 2024)
Background: The World Health Organization (WHO) published the Global Action Plan 2017-2025 seven years ago to address the dementia burden for those impacted, including persons living with dementia, their families, and health-care providers. There were seven action areas in the global action plan; the least achieved was action area seven (dementia research and innovation). The primary objective of the study was to assess the top 10 dementia research priorities among healthcare professionals, patients, caregivers, the public, and stakeholders to develop the Qatar National Dementia Research Plan. Methods: Convenience sampling was used in this cross-sectional survey. The study was conducted online with the involvement of HMC staff (physicians, nurses, and allied health staff) from all HMC facilities, patients and caregivers from Rumailah Hospital's Geriatric Department, and the public who attended the 2022 Advanced Dementia Research Conference. The survey was conducted during 22nd of October 2022 till April 31, 2024. Overall, 2000 participants provided their responses, which included health care professionals under HMC, including physicians, nurses, allied health staff, patients, caregivers, the public, and stakeholders in Qatar. Results: Dementia Risk Reduction (79%) was the top priority for the survey participants. The remaining nine priorities were the impact of early treatment (76%), health system capacity (73%), implementation of best practices for care (73), access to information and services post-diagnosis (71), caregiver support (70%), emotional well-being (67%), care provider education (65%), end-of-life care (65%), and non-drug approaches to managing symptoms (65%). Conclusion: The survey results clearly indicated that most participants ranked Dementia Risk Reduction as their top priority, indicating the essential focus on dementia prevention. These findings, together with goals such as early treatment, healthcare system capacity, and caregiver support, highlight the importance of an integrated, multidisciplinary approach to dementia management.